OBSTACLES TO DIDACTIC COMMUNICATION IN PHYSICAL EDUCATION LESSONS AMONG AL-HAIDARIYAH TEACHERS - Fadel Abbas, Diaa; Sami Yasser, Zaid (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The study aimed to identify the obstacles to didactic communication in physical education lessons within government schools in Al-Haidariyah, as perceived by physical education teachers. The study was conducted on a stratified random sample of 30 physical education teachers from Al-Haidariyah.To achieve the research objectives, the researchers developed a questionnaire to assess the obstacles in physical education lessons from the teachers’ perspectives. The validity and reliability of the questionnaire were verified after undergoing expert review. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS).The results revealed that the obstacles to didactic communication in physical education lessons were perceived to be significantly high. Additionally, there were statistically significant differences in the mean responses of the sample participants based on their experience regarding these obstacles.